Catalytic Activity of a Bifunctional Catalyst for Hydrotreatment of Jatropha curcas L. Seed Oil - J. García-Dávila; E. Ocaranza-Sanchez; C. Sánchez; A. L. Martínez-Ayala (Journal of Spectroscopy)
The hydrotreating process of vegetable oils (HPVO) involves the transformation of vegetable oil triglycerides into straight chain alkanes, which are carried out by deoxygenation reactions, generating multiple hydrocarbon compounds, cuts similar to heavy vacuum oil. The HPVO is applied to Jatropha curcas oil on USY zeolite supported with gamma alumina and platinum deposition on the catalytic as hydrogenation component. The acid of additional activity of the supports allows the development of catalytic routes that the intervention of catalytic centers of different nature reaches the desired product. The products of the hydrotreating reaction with Jatropha curcas seed oil triglycerides were identified by Fourier transform infrared spectroscopy and by mass spectroscopy to identify and analyze the generated intermediate and final hydrocarbon compounds.